2018
DOI: 10.1016/j.jclepro.2018.04.094
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle impact comparison of different concrete floor slabs considering uncertainty and sensitivity analysis

Abstract: Environmental impacts of precast, composite and cast-in-situ slabs are conducted. All life cycle stages from cradle-to-grave (including end-of-life stage) are included. Both midpoint and endpoint of LCA results are analyzed. The floor slabs are designed based on two functional units. Uncertainty analysis and sensitivity analysis are carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…e curing time of all components is not less than 12 h. In addition, the normal working hours of workers are eight hours a day. e optimization objective is to minimize the storage time and delivery delay time of finished components, as shown in (1).…”
Section: Verifying the Effectiveness Of Milpmentioning
confidence: 99%
See 1 more Smart Citation
“…e curing time of all components is not less than 12 h. In addition, the normal working hours of workers are eight hours a day. e optimization objective is to minimize the storage time and delivery delay time of finished components, as shown in (1).…”
Section: Verifying the Effectiveness Of Milpmentioning
confidence: 99%
“…Because of the drawbacks of conventional on-site construction approaches, the construction sector consumes approximately 40% of the total global energy, uses 40% of the global materials, and produces 50% of the global waste [1]. Many countries or regions, in recent years, have shown increasing interest in prefabrication as an "efficient" production strategy to meet their enormous construction demands [2].…”
Section: Introductionmentioning
confidence: 99%
“…Global warming and air pollution become one of the environmental issues facing the world. According to the World Business Council for Sustainable Development (WBCSD) [1] it has been reported that the construction sector consumes about 40% of total global energy. Another impact of the concrete industry on the environment is related to waste production.…”
Section: Life Cycle Assessment (Lca) Analysis Of Concrete Slab Constrmentioning
confidence: 99%
“…According to Lopez-Mesa [1] the environmental impact of a building with precast concrete slabs is about 12.2% lower than cast plates in place. It can be concluded that concrete slabs have a greater influence on environmental pollution.…”
Section: Life Cycle Assessment (Lca) Analysis Of Concrete Slab Constrmentioning
confidence: 99%
“…Some researchers established life cycle assessment (LCA) models of building construction from three aspects: environment [10], economy [11], and society [12]. For the construction of prefabricated buildings, the environmental impacts of three different concrete floor slabs have been quantified [13]. In order to improve social abilities of buildings, stakeholder analysis [14] was adopted in some projects.…”
Section: Introductionmentioning
confidence: 99%